PREVENTION OF COMPLICATIONS OF CARDIOVASCULAR DISEASES BY ORGANIZING MORPHOLOGICAL AND CLINICAL INDICATORS OF ARCUS SENILIS (Modern education and development, 2025)
cardiovascular disease is one of the biggest risk factors for human health. These diseases are one of the main causes of death and disability worldwide, and their prevention and early diagnosis are among the most pressing tasks of today's medicine. The development of cardiovascular diseases depends on many factors, among which are atherosclerosis, arterial hypertension, diabetes, hyperlipidemia, etc. At the same time, complications of diseases often reduce the quality of life of patients and require complex medical procedures. Therefore, new diagnostic tools and approaches are being sought for the early detection and Prevention of diseases.